2020
DOI: 10.21315/aamj2020.25.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Linking Cooperative Psychological Climate, Harmonious Passion, and Servicing Empowerment with Innovative Work Behaviour

Abstract: Innovative work behaviour (IWB) forms an essential basis for obtaining competitive advantage and long-term success for the hospitality firms. Nonetheless, empirical research on this potential behaviour has received limited attention in hospitality research. Drawing from self-determination theory (SDT), this study tests a conceptual model that examines the mediating role of harmonious passion between cooperative psychological climate and IWB within the hospitality industry. This study also recognises the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Such as, it has been considered to be a critical part for firm’s to remain competitive in the global market (Montani et al , 2017), enhancing service quality and meeting customers’ expectations (Luoh et al , 2014). Given the multiple benefits, scholars in different sectors such as knowledge intensive industries (Afsar and Rehman, 2015), education sector (Hosseini and Haghighi Shirazi, 2021), defence organizations (Caniels and Veld, 2016), multinational companies (Usmanova et al , 2020), education sector (Runhaar et al , 2016) and hospitality (Jan and Zainal, 2020) have investigated the various factors that can enhance IWB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such as, it has been considered to be a critical part for firm’s to remain competitive in the global market (Montani et al , 2017), enhancing service quality and meeting customers’ expectations (Luoh et al , 2014). Given the multiple benefits, scholars in different sectors such as knowledge intensive industries (Afsar and Rehman, 2015), education sector (Hosseini and Haghighi Shirazi, 2021), defence organizations (Caniels and Veld, 2016), multinational companies (Usmanova et al , 2020), education sector (Runhaar et al , 2016) and hospitality (Jan and Zainal, 2020) have investigated the various factors that can enhance IWB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these eight studies, four articles provide empirical evidence regarding the relationship factor and IWB and found a positive relationship between the two variables. 55 , 57 , 66 , 71 Two articles provided evidence that IWB in the service sector is positively impacted by engagement. 47 , 72 Additionally, scholars did not discover a significant link between the positive emotion factor and IWB in the service industry, particularly in the hotel industry.…”
Section: Resultsmentioning
confidence: 99%
“…This emotion will encourage employees to demonstrate greater creativity and innovation at work, and it will, in turn, inspire them to create new values and new motivations. Finally, it has been shown that work passion can positively affect EIB [ 52 ], providing a continuous stream of positive emotional resources for employees to implement innovative activities [ 53 ]. In summary, work passion contributes to the formation of creativity.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%